On the use of citizen science in the agricultural sector; BIO Web of Conferences; Vol. 67 : Vavilov readings-2023 (VVRD 2023) - Botygin I. A. Igor Aleksandrovich; Goncharova N. A. Natalya Aleksandrovna; Sherstneva A. I. Anna Igorevna; Sherstnev V. S. Vladislav Stanislavovich (2023, 2023)
Title screen